"What's on Your Mind?" Examining the Influence of Facebook User Motivations, Usage Intensity, and Public Self-Disclosure on Perceived Social Capital. Issue 3 (2nd July 2020) - Castillo, Ryan P.
ABSTRACT: This study examines the influence of user motivations and behaviors on perceptions of mutually beneficial social resources accessible via connections formed and maintained on Facebook. Survey data collected from undergraduate Facebook users were used to construct a multiple-group structural equation model of male (n = 109) and female (n = 187) users to assess the effects of motivations, usage intensity, and general public self-disclosure on users' perceptions of bridging and bonding social capital. Results indicate that status and relationship formation motivations directly affect both dimensions of social capital for all users. Formation motivation was found to positively affect public self-disclosure for male users, and usage intensity was found to mediate the positive effect of user motivations on public self-disclosure for both groups. General self-disclosure on public Facebook profiles was found to positively affect perceived bridging capital and mediated the effect of formation motivation on bridging capital only for male users, while public self-disclosure was not found to significantly predict either dimension of social capital among female users. Findings are discussed within the theoretical framework of social capital and the hyperpersonal model of computer-mediated communication, and directions for future research are proposed.